Solving the Traveling Salesman Problem on a Directed Graph Using Greedy Algorithm (Case Study: Locations of BRI Bank in Bandar Lampung City) - Nurfabella, Rehsya; Chasanah, Siti Laelatul; Notiragayu (Integra: Journal of Integrated Mathematics and Computer Science, 2024)
The traveling salesman problem is the idea that a salesman must discover the shortest path between an origin point and many destination points, returning to the origin point after visiting the destination point once. In this study, the Greedy Algorithm will be used to solve the Traveling Salesman Problem on a directed graph which represented BRI Banks in Bandar Lampung city. The locations of the banks are represented by points, while the journey time between BRI Banks is represented by lines. According to the results, 130 minutes was the same amount of time spent manually and with the Python software.